2021
DOI: 10.3390/diagnostics11101799
|View full text |Cite
|
Sign up to set email alerts
|

The Histopathological Correlate of Peri-Vascular Adipose Tissue Attenuation on Computed Tomography in Surgical Ascending Aorta Aneurysms: Is This a Measure of Tissue Inflammation?

Abstract: On computed tomography (CT) imaging, a peri-vascular adipose tissue attenuation (pVAT) measure has been proposed as a non-invasive correlate of inflammation in the coronary artery vessels, and a single research group provided histopathological demonstration of this radiological/pathological correspondence. Our group has shown that patients with surgical-grade ascending aorta (AA) aneurysm display higher pVAT compared with patients with smaller aneurysms or normal AA. Based on histopathological studies on coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…It has been widely demonstrated that pFAI correlates with plaque attenuation components in patients with non-ST-elevation acute coronary syndrome. Antonopoulos et al [ 21 ] firstly reported that the detection and quantification of coronary inflammation is a useful noninvasive imaging biomarker of perivascular inflammation and immune activation which are known to be important determinants of plaque vulnerability Our results are in agreement with those of Gaibazzi et al [ 14 ], who found higher pFAI values in patients with non-obstructive coronary arteries. Interestingly, in accordance with Gaibazzi et al [ 14 ], we also found in our small population of 15 patients with CAD-RADS ≤ 1 and pFAI ≥ −70 HU higher rates of hypertension and smoke habit.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It has been widely demonstrated that pFAI correlates with plaque attenuation components in patients with non-ST-elevation acute coronary syndrome. Antonopoulos et al [ 21 ] firstly reported that the detection and quantification of coronary inflammation is a useful noninvasive imaging biomarker of perivascular inflammation and immune activation which are known to be important determinants of plaque vulnerability Our results are in agreement with those of Gaibazzi et al [ 14 ], who found higher pFAI values in patients with non-obstructive coronary arteries. Interestingly, in accordance with Gaibazzi et al [ 14 ], we also found in our small population of 15 patients with CAD-RADS ≤ 1 and pFAI ≥ −70 HU higher rates of hypertension and smoke habit.…”
Section: Discussionsupporting
confidence: 91%
“…Antonopoulos et al [ 21 ] firstly reported that the detection and quantification of coronary inflammation is a useful noninvasive imaging biomarker of perivascular inflammation and immune activation which are known to be important determinants of plaque vulnerability Our results are in agreement with those of Gaibazzi et al [ 14 ], who found higher pFAI values in patients with non-obstructive coronary arteries. Interestingly, in accordance with Gaibazzi et al [ 14 ], we also found in our small population of 15 patients with CAD-RADS ≤ 1 and pFAI ≥ −70 HU higher rates of hypertension and smoke habit. With the exception of age and diabetes, the rates of cardiovascular risk factors in our small subgroup were similar to the LAP group, suggesting that cardiovascular risk factors may alter pericoronary fat, leading with time to unfavorable plaques.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several studies have indirectly suggested that inflammation is involved in atrial fibrillation, however, direct evidence of local inflammatory activity in the atria of patients with AF is scarce [8][9][10][11][12][13][14]. We hypothesized that the density of adipose tissue, also defined as "attenuation" when measured with CCTA, in close anatomic continuum with the LA, may be considered as a marker of the local inflammatory status, similarly to what has been previously demonstrated for peri-vascular adipose tissue attenuation and vascular inflammation [15][16][17][18][19][20]. The assessment of the mean density of adipose tissue in continuum with the LA will confirm (or contradict) such atrial inflammatory involvement in AF, using in-vivo imaging.…”
Section: Introductionmentioning
confidence: 90%